Immunity in athletes - Pedersen, B. K.; Rohde, T.; Zacho, M. (The Journal of Sports Medicine and Physical Fitness, 1996)
It has become clear that the immune system responds to increased physical activity and may be given some of the credit for exercise-related reduction in illness. In contrast, it has repeatedly been shown that intense exercise causes immunosuppression. In essence the immune system is enhanced during moderate and severe exercise, and only intense long-duration exercise is followed by immunodepression. The latter include suppressed concentration of lymphocytes, suppressed natural killer and lymphokine activated killer cytotoxicity and secretory IgA in mucosa. Whether or not the "open window" in the immune system occurs is dependent on the intensity and duration of exercise. One reason for the "overtraining effect" seen in elite athletes could be that this window of opportunism for pathogens is longer and the degree of immunosuppression more pronounced. It is being hypothesized that severe immunodepression may occur if athletes does not allow the immune system to recover, but initiate a new bout of exercise while still immunodepressed. It has also been suggested that neutrophils serve as a last line of defence. The removal of this back-up system following extreme activity would be compatible with the propensity of "overtrained" individuals to develop upper respiratory tract infections.